Multidisciplinary Rehabilitation Programs To Enhance Daily Living Activities And Quality Of Life In Elderly Patients With Parkinson’s Disease: A Review Study (The Review of Diabetic Studies, 2024)
Background: Parkinson's disease (PD) is a neurodegenerative disorder with progressive characteristics that affects 10 million people globally, having a prevalence of 1–2% in people over 65 years old. Motor and non-motor symptoms impair activities of daily living (ADL) and quality of life (QoL), particularly in older patients, with comorbidities exacerbating decline. Multidisciplinary rehabilitation programs (MRPs) integrate physiotherapy, occupational therapy, speech therapy, and psychological intervention to address these challenges holistically. Aim: This review evaluates the effectiveness of MRPs in enhancing ADL and QoL in older PD patients (ages ≥65, Hoehn and Yahr stages 2–4). Methods: Systematic search of PubMed, Cochrane, and Web of Science (2004–2024) identified 45 RCTs and reviews. Outcomes were ADL (UPDRS-II, FIM) and QoL (PDQ-39). Narrative synthesis and GRADE assessed evidence. Results: Inpatient MRPs significantly improved ADL (SMD 0.69, 95% CI -0.13 to 1.51) and QoL (SMD 0.39, 95% CI 0.06–0.72), with effects lasting up to 12 months. Outpatient programs showed moderate effect sizes (SMD 0.45) but were marred by adherence issues. Intensity and tailoring were both important moderators. Conclusion: MRPs, especially inpatients, enhance ADL and QoL, delaying dependency. Large-scale RCTs and new delivery modes (e.g., tele-rehabilitation) are required to optimize access and impact.